Molecular and metabolic insights into muscle development and feed efficiency in beef cattle - Ascolese, Sophia M.; Voy, Brynn H.; Beever, Jonathan E.; Stephens, Laney M.; Myer, Phillip R. (Frontiers in Animal Science, 2025)
As global demand for animal protein rises, improving feed efficiency in beef cattle has become a central focus for sustainable livestock production. Feed efficiency, often quantified through residual feed intake (RFI), is a complex trait influenced by genetic, physiological, and environmental factors. Among these, skeletal muscle plays a pivotal role due to its central function in growth, metabolism, and nutrient utilization. This mini-review explores the molecular and metabolic mechanisms linking muscle development to feed efficiency, highlighting recent advances in gene expression profiling, hormone signaling, and energy metabolism. Studies have identified key genes and pathways, such as those involved in the electron transport chain and insulin-like growth factor 1 (IGF1) signaling, that contribute to muscle growth and efficient energy use. Additionally, the role of the rumen microbiome in modulating nutrient absorption and its interaction with host muscle metabolism is discussed. Integrating these insights with genomic selection tools provides a promising avenue for enhancing feed efficiency while maintaining production goals. Understanding the biological foundations of muscle development offers valuable opportunities to refine genetic selection and management practices for a more profitable and environmentally sustainable beef industry.